The effect of cilostazol and aspirin pre-treatment against subsequent transient focal cerebral ischemia in rat. (November 2014) - Toda, Yusuke; Katsura, Ken-ichiro; Saito, Moeko; Inaba, Toshiki; Sakurazawa, Makoto; Katayama, Yasuo
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Among several anti-platelet drugs to prevent recurrent stroke, cilostazol has shown various effects besides its anti-platelet activity. We examined whether 7 days of oral administration of cilostazol protects against subsequent cerebral ischemia, and whether or not the effect of combination therapy with aspirin is more protective. Methods: We used Sprague-Dawley (SD) rats and assigned them to four groups: vehicle, aspirin, cilostazol, and aspirin plus cilostazol combination therapy. After oral administration of anti-platelets for 7 days, we performed transient middle cerebral artery occlusion (MCAO) for 90 minutes, and examined infarct volume, neurological symptoms, and regional cerebral blood flow (rCBF). Immunostaining of Bax, Bcl-2, TUNEL, 4-HNE, 8-OHdG, and COX-2 was performed 24 hours after ischemia. Results: The cilostazol group and the combination therapy group showed significant decreases of infarct volume and significant improvements of rCBF during ischemia, compared with the vehicle or aspirin group. Significant decreases of Bax, TUNEL, 8-OHdG, and 4-HNE expression in the combination therapy group, compared with those in the vehicle or aspirin group, were shown in the boundary zone. COX-2 expression was unexpectedly increased in the combination therapy group. Discussion: Aspirin co-administration did not inhibit this effect. The addition of the oral administration of cilostazol either alone or with aspirin administration may be beneficial for subsequent cerebral ischemic damage in terms of reducing infarct volume, improving rCBF during ischemia, inhibiting the apoptotic pathway, and reducing oxidative stress.